The neoliberal firm and nested subsumption: Labour process transformations in the NYC taxi industry. (August 2015) - Mathew, Biju
In this paper I use New York's taxi industry and the struggle around GPS technologies to articulate some essential aspects of a new regime of labour subsumption that is taking shape, most evidently in cities. I argue that these new aspects of labour subsumption may be useful in understanding changes in labour regimes across industries in the neoliberal period. Finally, I attempt to demonstrate connections between theories of labour subsumption and practices of labour organising. I contend that labour subsumption theory and specific forms of labour organisation show a clear relationship in the past and thus, if we are able to discern significant developments in the modes by which capital subsumes labour in the present neoliberal period, this could offer new insights in the domain of labour organising strategies.